Synthesis of an Instructional Model Using Blended Learning with Collaborative Learning to Enhance English Reading Ability of English Teaching Program Students in the Faculty of Education, Rajabhat Universities - Langprayoon, Patthaporn; Songserm, Ubonwan (วารสารสันติศึกษาปริทรรศน์ มจร, 2023)
The objectives of this research were 1) to study English reading abilities and problems of English Teaching Program students in the Faculty of Education at Rajabhat Universities and 2) to synthesize the instructional model by using blended learning with collaborative learning to enhance English reading abilities of English Teaching Program students in the Faculty of Education at Rajabhat University. This research was mixed-method research, and the research instruments used in this study were the documentary, questionnaire, and semi-structured interview. The statistics used in this study were content analysis, means, and standard deviation (S.D.). The research results were found that 1. The students had problems in English reading in the highest level. 2.The instructional model using blended learning with collaborative learning to enhance English reading ability (PICCA Model) consisted of 4 factors: 1) theories 2) objectives 3) steps in teaching consisted of 5 steps 3.1) Preparation: P 3.2) Instruction: I 3.3) Collaboration: C 3.4) Checking: C 3.5) Assessment: A and 4) assessment and evaluation.